Migraine - Clinical Approach, Assessment and Rare Homoeopathic Remedies (Homoeopathy for All, 2021)
Migraine is the most common disabling primary headache disorder globally. [3] It is a common, multifactorial, disabling, recurrent, hereditary neurovascular headache disorder. It is characterized by recurrent attacks. Attacks typically present with unilateral, throbbing headache with associated symptoms including nausea, multi-sensory hypersensitivity, and marked fatigue.[3] Several treatment principles, including taking medications early in an attack and using a stratified treatment approach, can help ensure that migraine treatment is cost effective.[2]
Keywords: globally; medications; stratified